Disorders of gait pattern in children with cerebral palsy - Dudek, Joanna; Chuchla, Magdalena; Snela, Sławomir; Szymczyk, Daniel; Drużbicki, Mariusz (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In clinical decision-making in children with cerebral palsy quantitative studies are needed to allow an objective assessment of motor behavior. The article contains a brief review of basic aspects connected with development of bipedal locomotion, normal gait, and gait disorders in cerebral palsy. The main attention is given to the description of the most specific gait disorder categories within the single segments and the complex patterns of several joints, and multiple levels. Described examples doesn’t provide a complete list of all gait patterns and relationships that occur in person with cerebral palsy. They illustrate the framework for the interpretation of gait data, which allow for better understanding the problems and possible causes of motor disorders.